Lifting the curtain on our knowledge on New Guinean Benstonea (Pandanaceae) - Callmander, Martin W.; Keim, Ary P.; Heatubun, Charlie D.; Homot, Peter; Buerki, Sven (Phytotaxa, 2016)
New Guinea is one of the centres of diversity of Benstonea (Pandanaceae), a genus distributed from India to Fiji. Ten species were previously recognised on this island and further field observations, accompanied by the study of available herbarium material have brought new insights into species delimitations within a group of caespitose species with a solitary terminal infructescence. The taxonomical identity of Benstonea odoardoi is elucidated and is considered here as a synonym of Benstonea lauterbachii. Three new combinations and a new name—based on names of Pandanus species previously treated as synonyms of Benstonea odoardoi—are proposed for four distinct species belonging to this group of caespitose species and restricted to Indonesian New Guinea and Papua New Guinea. Finally, Pandanus bintuniensis is here considered as a synonym of Benstonea permicron.